Improving the Teaching of Persian Verse Literature for non-Persian Speakers: A Comprehensive Evaluation of Educational Materials - Amirreza Vakilifard; Fatemeh Janatirad; Zoya Rezaei Mahalati (مطالعات زبانی و بلاغی)
The assessment of textbooks, thoughtfully considering the requirements and aims inherent to the realms of pedagogy and learning, plays a pivotal role in refining the educational process. Furthermore, it yields invaluable insights that inform pedagogical planning and classroom management. Within the specific context of imparting Persian literature to non-Iranian students, an apparent scarcity prevails concerning educational materials underpinned by substantial scholarship. Moreover, the available literature lacks a comprehensive scholarly examination. This research is dedicated to evaluating the prospective efficacy of an educational textbook tailored for foreign students, with a particular focus on the realm of literary education. The textbook in question, entitled Teaching Books of Persian Verse Literature (Volume 1), is from the esteemed Fārsināma Collection and is assessed through the discerning eyes of Persian literature instructors. The methodological approach employed here entails a custom-crafted questionnaire encompassing 12 primary sections, each comprising 60 distinctive items. It is essential to note that this questionnaire underwent a rigorous process of validation and reliability assessment. A total of 29 participants, Persian language and literature instructors, contributed to this research, with a distribution of 18 females and 11 males. These educators, aged between 25 and 45, have accumulated approximately five years of teaching experience in their field. The comprehensive analysis of the data culminates in notable findings, affirming the commendable desirability of the textbook designed to facilitate the instruction of Persian literature for non-Persian speakers. Notably, the findings indicate that the section dedicated to specialized literary education assumes the highest rank among the 12 sections subject to evaluation. Furthermore, the domains of listening, speaking, reading, and writing skills also secure a prominent position in the hierarchy of desirability. The ramifications of this research extend beyond the enhancement of educators' awareness regarding the affirmative attributes and limitations of the textbook. It concurrently beckons authors to undertake the composition of pedagogical materials that bear the hallmarks of greater scholarly rigor and suitability, thus contributing significantly to the advancement of the discourse within the pedagogical domain.